The Role of Lactate Exercise Test and Fasting Plasma C-Peptide Levels in the Diagnosis of Mitochondrial Diabetes: Analysis of Clinical Characteristics of 12 Patients With Mitochondrial Diabetes in a Single Center With Long-Term Follow-Up - Zhao, Yuan; Zhang, Ying; Qi, Mengya; Ping, Fan; Zhang, Huabing; Xu, Lingling; Li, Wei; Li, Yuxiu (Frontiers in Endocrinology, 2022)
Objective: The aim of this study was to analyze the clinical characteristics and the pattern of long-term changes of fasting plasma C-peptide in patients with mitochondrial diabetes (MD), and to provide guidance for the diagnosis and treatment of MD. Methods: We retrieved MD patients with long-term follow-up at Peking Union Medical College Hospital from January 2005 to July 2021 through the medical record retrieval system and retrospectively analyzed their clinical data, biochemical parameters, fasting plasma C-peptide, glycosylated hemoglobin and treatment regimens. Results: A total of 12 MD patients were included, with clinical characteristics of early-onset, normal or low body weight, hearing loss, maternal inheritance, and negative islet-related autoantibodies. In addition, patients with MD exhibited significantly higher mean plasma lactate levels during exercise compared to controls (8.39 ± 2.75 vs. 3.53 ± 1.47 mmol/L, p=0.003) and delayed recovery time after exercise (6.02 ± 2.65 vs. 1.93 ± 1.04 mmol/L, p=0.011). The fasting plasma C-peptide levels decreased as a negative exponential function with disease progression (Y= 1.343*e -0.07776X, R2=0.4154). Treatment regimens in MD patients were varied, with no metformin users and a weak correlation between insulin dosage and body weight. Conclusions: The increased level of plasma lactate during exercise or its delayed recovery after exercise would contribute to the diagnosis of MD. Changes of fasting plasma C-peptide in MD patients over the course of the disease indicated a rapid decline in the early stages, followed by a gradual slowing rate of decline.